Infectious peritonitis profile in peritoneal dialysis at Ibn Sina University Hospital: a 6-year data report - Bekaoui, Samira (Dove Medical Press, 2014)
BACKGROUND: Infectious peritonitis (IP) is the most common complication in peritoneal dialysis (PD). The purpose of this study is to assess the prevalence of IP and to determine its clinical, biological, and evolutive characteristics. PATIENTS AND METHODS: We conducted a five year, five months retrospective study from July 2006 to December 2011. All patients on peritoneal dialysis that have been followed on PD for a minimum of 3 months and who presented IP during follow-up were included. Data were analyzed using SPSS 17.0. RESULTS: The 76 episodes of IP were identified in 36 patients. The peritonitis rate (months × patients/peritonitis), as calculated by the Registre de Dialyse Péritonéale de Langue Française (RDPLF Registry) [French peritoneal dialysis registry] in December 2011, was 18.59. Time to occurrence of peritonitis from the start of peritoneal exchange was 15.44±10 months. The mean age of our patients was 49.1±16.8 years [10–80]: the youngest patient’s age was 10, while the oldest was 80 years old (male to female: sex ratio M/F=1,66). Also, 22% of our patients were diabetic. The mean follow-up in PD was 22.6±14 months. Abdominal pain was present in 79% of the cases. Fever and vomiting were noted in 42% and 38% of cases, respectively. The C-reactive protein rate was elevated in 77% of cases, and leukocytosis was found in 27% of cases. Bacteriological proof was present in 73.68% of cases. Gram-positive cocci were involved in 56.6% of microbiologically proven IP cases. Gram-negative bacilli were represented in 37.7%. The outcome was favorable in 89.4%. The PD catheter was removed in 2.63% of the cases. In addition, 7.89% of our patients were transferred to hemodialysis. DISCUSSION: The rate of IP remains high in our series. More than one-half of the peritonitis cases with positive cultures (56.6%) were caused by Gram-positive cocci. Gram-negative bacilli ranked second (27.7%). These results agree with data in the literature. Moreover, the rate of culture-negative IP in our series is high (26%). Evolution is good in most cases (89%). CONCLUSION: Despite the gradual decrease of its rate, peritonitis remains frequent in our center and calls for optimization of means of prevention. The high frequency of negative culture IP in our study urges us toward better collaboration with biologists to target antibiotic therapy and improve IP management.